Anemia in the patients with acute myeloid leukemia revisited: Prognostic importance of anemia on treatment-naïve patients - Çınar, Olgu Erkin; Malkan, Ümit Yavuz; Aladağ, Elifcan; Demiroğlu, Haluk; Büyükaşık, Yahya; Göker, Hakan; Haznedaroğlu, İbrahim Celalettin (Acta Medica, 2025)
Objective: To determine the independent prognostic influence of pre-treatment anemia severity in patients with acute myeloid leukemia. Patients and Methods: This was a retrospective evaluation of AML patients between January 2002 and May 2018 at a university hospital hematology clinic. The patients were divided into four groups: intensive treatment achieving complete remission (CR), intensive treatment without CR, non-intensive treatment, and supportive treatment. Baseline clinicodemographic features, laboratory data including serum hemoglobin levels, were collected. Baseline and post-treatment hemoglobin levels were compared according to treatment and across groups. A logistic regression analysis was also made to evaluate the influence of anemia on achieving a complete remission. Results: The mean hemoglobin level at the time of diagnosis was 8.5 g/dL (6.4 – 14.4). Although hemoglobin value was lower in the secondary AML subgroup, there was no significant difference between the groups at the time of diagnosis (p = 0.082). Hemoglobin values after induction chemotherapy were significantly different between treatment groups (p <0.001). When the variables predicting complete remission are examined by logistic regression, per 1 gr/dL increase in hemoglobin level at the time of diagnosis increased the probability of remission significantly (p = 0.047, OR = 1.13, 95% CI 1.07 - 1.24). Conclusion: A patient’s baseline pre-treatment serum hemoglobin level can predict the achievement of complete remission in AML patients. Anemia improves with induction chemotherapy, even without complete remission.